The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1600-0765.2007.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of cranberry polyphenol on biofilm formation and cysteine proteases of Porphyromonas gingivalis

Abstract: These findings indicate that the polyphenol fraction inhibits biofilm formation and the Arg-gingipain and Lys-gingipain activities of P. gingivalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 34 publications
1
49
0
3
Order By: Relevance
“…This result is of interest because AC-PACs did not seem to have antibiotic properties, even at the highest concentration tested, which would limit the development of resistance to them and would not disturb the oral ecology. The inhibition of biofilm formation by an uncharacterized polyphenol extract prepared from cranberry has been previously reported for Streptococcus mutans and P. gingivalis (5,11,31,45).…”
Section: Discussionmentioning
confidence: 99%
“…This result is of interest because AC-PACs did not seem to have antibiotic properties, even at the highest concentration tested, which would limit the development of resistance to them and would not disturb the oral ecology. The inhibition of biofilm formation by an uncharacterized polyphenol extract prepared from cranberry has been previously reported for Streptococcus mutans and P. gingivalis (5,11,31,45).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, researches have explored many biological activities of plants extracts for treatment of various diseases (13,16,22). For inhibition of oral pathogens, many plant extracts have been reported to have the potential on this purpose, for example, ethyl acetate extract of Camellia sinensis leaves was reported to decrease the incidence of dental caries (23) whereas water extract of Vaccinium macrocarpon fruits showed an inhibitory effect against protease enzyme of Porphyromonas gingivalis (24). Moreover, the extract from Salvadora persica stem can inhibit many oral pathogenic bacteria, such as S. mutans, Lactobacillus acidophilus, Aggregatibacter actinomycetemcomitans, and P. gingivalis (25).…”
Section: Discussionmentioning
confidence: 99%
“…These biological activities have mainly been attributed to the polyphenol fraction. Polyphenols are naturally present in a number of foods and drinks, such as tea (12), coffee (5), wine and grape juice (3,33), beer and hops (32), cranberry juice (11,34,36,37), cocoa (23), apple juice (38), and many others (28). In a previous study, we have also shown that people who regularly consume foods and drinks containing polyphenols have lower levels of culturable bacteria in their saliva and dental plaque (27).…”
mentioning
confidence: 99%